2020
DOI: 10.3389/fphar.2020.00270
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: microRNA-155 Modulates Hepatic Stellate Cell Proliferation, Apoptosis, and Cell Cycle Progression in Rats With Alcoholic Hepatitis via the MAPK Signaling Pathway Through Targeting SOCS1

Abstract: The aim of this study was to investigate the regulatory function of the non-coding microRNA-155 (miR-155) and suppressor of cytokine signaling 1 (SOCS1) in alcoholic hepatitis (AH) and its potential mechanism associated with the mitogen-activated protein kinase (MAPK) signaling pathway. Levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), albumin (ALB), total bilirubin (TBIL), malondialdehyde (MDA), and superoxide dismutase (SOD) were measured in a rat model of AH. The biological predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…It was previously reported that miR-155 was involved in the mediation of the MAPK signaling pathway (22). Moreover, miR-155 played a critical role in regulating inflammatory responses through the MAPK signaling pathway (23). Therefore, the present findings of intercorrelation between miR-155 and the MAPK signaling pathway in the regulation of inflammatory processes are consistent with a range of previous results in other systems.…”
Section: Discussionsupporting
confidence: 92%
“…It was previously reported that miR-155 was involved in the mediation of the MAPK signaling pathway (22). Moreover, miR-155 played a critical role in regulating inflammatory responses through the MAPK signaling pathway (23). Therefore, the present findings of intercorrelation between miR-155 and the MAPK signaling pathway in the regulation of inflammatory processes are consistent with a range of previous results in other systems.…”
Section: Discussionsupporting
confidence: 92%
“…In response to external injurious stimul, quiescent HSCs undergo a complex activation process including downregulation of vitamin A, de novo expression of the cytoskeletal protein α‐smooth muscle actin (α‐SMA) and redundant production of ECM components such as α1(I)collagen (COL1α1), and differentiate into proliferating myofibroblast‐like cells (Kisseleva & Brenner, 2021; Pellicoro, Ramachandran, Iredale, & Fallowfield, 2014). Some tumor suppressor genes, including suppressor of cytokine signaling 1 (SOCS1) and tumor protein 53 (P53), have been found to be involved in the process of liver fibrosis (Ahsan & Mehal, 2014; Jin et al, 2016;Kandhi et al, 2016; Liu et al, 2020). Liver tissues in SOCS1‐deficient mice show increased expression of genes coding for α‐SMA, COL1α1 and enzymes involved in remodeling the ECM.…”
Section: Introductionmentioning
confidence: 99%
“…Liver tissues in SOCS1‐deficient mice show increased expression of genes coding for α‐SMA, COL1α1 and enzymes involved in remodeling the ECM. And primary HSCs from SOCS1‐deficient mice show enormous proliferative capacity in response to growth factors (Kandhi et al, 2016; Liu et al, 2020). Moreover, down‐regulation of P53 enhances the proliferation of HSC lines and primary cells, while an increase of P53 inhibits HSC proliferation (Ahsan & Mehal, 2014; Jin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Treatments for ALF are limited to orthotopic liver transplantation and the use of artificial livers in the clinic, both of which are highly invasive. MicroRNA‐155 (miR‐155) has been shown to aggravate liver injury (Liu et al., 2020; Zhang et al., 2019). Downregulation of miR‐155 by antisense oligonucleotides (ASOs) of miR‐155 (miR155‐ASOs) was reported to alleviate septic liver injury by inhibiting oxidative stress (Yang et al., 2018), suggesting these molecules are promising therapeutic drugs for ALF.…”
Section: Introductionmentioning
confidence: 99%